1987
DOI: 10.1111/j.1529-8817.1987.tb02539.x
|View full text |Cite
|
Sign up to set email alerts
|

ARAGONITE CRYSTALS IN SPIROGYRA SP. (CHLOROPHYTA)

Abstract: Intracellular crystals of aragonite have been identified by selected area electron diffraction (SAED) in a species of the freshwater filamentous alga Spirogyra from the Thames River, Ontario, Canada. The crystals are 2 to 24 μm in diameter, and characterized by a unique cross‐shaped morphology, in which needle‐like, or prismatic outgrowths develop from a common axis. Crystals may be dispersed throughout filaments, but tend to cluster as aggregates towards the centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
0
7
0
2
Order By: Relevance
“…The chemical composition of cruciate inclusions in Spirogyra was characterized as calcium oxalate by Klein (1877), Kamiya (1961), and Knobloch and Kalina (1968), but more recently Mann et al (1987) reported them to be aragonite. Considerable significance was attached to the purported finding of aragonite, being the first report of intracellular aragonite in a freshwater alga (Mann et al 1987).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The chemical composition of cruciate inclusions in Spirogyra was characterized as calcium oxalate by Klein (1877), Kamiya (1961), and Knobloch and Kalina (1968), but more recently Mann et al (1987) reported them to be aragonite. Considerable significance was attached to the purported finding of aragonite, being the first report of intracellular aragonite in a freshwater alga (Mann et al 1987).…”
Section: Discussionmentioning
confidence: 97%
“…Numerous authors (Klein 1877;Fischer 1884;Kamiya 1961;Knobloch and Kalina 1968;Mann et al 1987) have reported the presence of cruciate cellular inclusions in Spirogyra, but some of the specimens lacked the reproductive features necessary for definitive species identification. Those that could be identified were Spirogyra setiformis (Roth) Kü tzing (Fischer 1884) and Spirogyra ellipsospora Transeau (Transeau Fig.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…7). Here, it starts again at the 300 MHz level (r 0 ≈ 1.13 R ) and reaches the 50 MHz level at a height of 0.6 R above the photosphere after approximately 4 s. This motion would cause a type III radio burst with a drift rate of −63 MHz s −1 , which is a reasonable type III drift rate (Mann & Klassen 2002). Because of the decreasing global magnetic field, the Larmor energy is dramatically converted into drift energy (Fig.…”
Section: Numerical Treatment and Discussionmentioning
confidence: 87%
“…Частоту встречаемости видов оценивали по шестибальной шкале (Корде, 1956). Видовую идентификацию проводили с помощью определителей Mann, 1989Mann, , 1999Mann, Stickle, 1991Lange-Bertalot, 1995;LangeBertalot, Metzeltin, 1996;Krammer, 1997Krammer, , 2000Round, Basson, 1997;Zimmermann et al, 2010;Pavlov et al, 2013, и др. ).…”
Section: материалы и методыunclassified